Frontal osteitis complicated with post-traumatic knife osteonecrosis in sexual assault: A case report - Lungere Bazibuhe Prosper; Mongwa Mbikilile Justin; Kitumaini Munyahali John; Fataki Rutega Junior; Bandeke Matabishi Destin; Kavira Isse-Somo; Cikwanine Buhendwa; Alumeti Munyali Désiré (Chinese Journal of Plastic and Reconstructive Surgery, 2025)
Frontal osteitis complicated with bone necrosis is rare. In addition, the condition has various etiologies, such as frontal sinusitis, penetrating head injury, postoperative complications after sinus surgery, and hematogenous spread from distant sites. In frontal osteitis, early diagnosis is important, and fistulization of pus in the scalp or on the traumatized forehead may raise the suspicion of osteitis in one of the skull bones. The exclusion of osteonecrosis is such cases is an emergency; hence, a magnetic resonance imaging and a computed tomography scan are required in the absence of skull radiography. Early administration of the appropriate treatment in the immediate post-trauma period ensures effective prevention of frontal osteitis; however, the treatment of bone necrosis involves debridement and antibiotic therapy to prevent fatal intracranial complications. This report presents the case of a 16-year-old female patient who experienced sexual and physical assault that resulted in undetected frontal trauma complicated with frontal osteonecrosis. Thorough clinical examination of the patient was performed, and follow-up and multidisciplinary management enabled the social integration of the patient.